2016
DOI: 10.7717/peerj.2536
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenetic foraging activity and feeding selectivity of the Brazilian endemic parrotfishScarus zelindae

Abstract: Parrotfish are fundamental species in controlling algal phase-shifts and ensuring the resilience of coral reefs. Nevertheless, little is known on their ecological role in the south-western Atlantic Ocean. The present study analysed the ontogenetic foraging activity and feeding selectivity of the Brazilian endemic parrotfish Scarus zelindae using behavioural observation and benthic composition analyses. We found a significant negative relationship between fish size and feeding rates for S. zelindae individuals.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…For instance, interviews with local fishermen from the site evaluated in the present study confirmed this trend for many reef fish species, especially for Scarus trispinosus , an endemic and endangered parrotfish. This species is virtually extinct locally in shallow reefs, but being recorded at high abundance in the last decades [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, interviews with local fishermen from the site evaluated in the present study confirmed this trend for many reef fish species, especially for Scarus trispinosus , an endemic and endangered parrotfish. This species is virtually extinct locally in shallow reefs, but being recorded at high abundance in the last decades [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Carapitanga (8° 49'35.59 "S 35° 2'43.16" W) and Carapitanga do Norte (8° 49'13.58 "S and 35° 2'21.60" W) were the deep reefs. They are reefs more distant from the main land (around 8 km) and had a depth ranging from 25 to 30 m ( Fig 1 , also see [ 38 ] for site description).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is often assumed that when fish feed on a macroalga that it is the alga they are eating. This view led to the perception that parrotfishes eat macroalgae, including turf (e.g., Adam et al, 2015 ; Feitosa & Ferreira, 2015 ; Pereira et al, 2016 ). Our feeding observations indicate that while juvenile parrotfishes, i.e., Scarus schlegeli , S. ghobban , S. rivulatus , and Chlorurus spilurus , took many small bites from G. divaricata , they did not appear to consume the thallus itself.…”
Section: Discussionmentioning
confidence: 99%
“…Up until the 1980’s parrotfishes were rarely captured by recreational fishers and were not targeted by commercial fisheries. However, in the mid 1990’s parrotfish captures intensified in Northern and Northeastern Brazil (Ferreira et al, 2012; MMA, 2014; Roos et al, 2015), with widespread usage of gillnets, traps and spears, followed by a remarkable abundance decline of S. trispinosus at all studied locations (e.g., Francini-Filho & Moura, 2008a; Francini-Filho & Moura, 2008b; Bender et al, 2014; Pereira et al, 2016). Its population is estimated to have declined by >50% over the past three decades, and S. trispinosus is currently considered one of the world’s most endangered parrotfishes (Comeros-Raynal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%